PENGEMBANGAN SUMBER DAYA MANUSIA DI DINAS PENDIDIKAN KABUPATEN SUMEDANG - edi setiawan; Dini Meliani; Suherman (JRPA - Journal of Regional Public Administration, 2023)
The purpose of this study was to determine Human Resource Development at the Sumedang District Education Office. The method used in this research is a qualitative research method. The technique for determining research informants is purposive sampling. With research informants, namely the Head of the Personnel Section and 3 (three) people from the Sumedang District Education Office. Data collection techniques used are library research and field studies which consist of observation, interviews, documentation. While the data processing procedures in this study are data collection, data reduction, data display and drawing conclusions/verification. Based on the results of the study it was concluded that Human Resource Development at the Sumedang Regency Education Office had not gone well. This is because there are several obstacles, namely the availability of the budget for training is still limited, the training facilities and infrastructure are still inadequate, and there are still many employees who have not attended the education and training program (training). Efforts to overcome this by proposing facilities and infrastructure to the Province and budgeting special funds to purchase training needs facilities and infrastructure as well as involving employees to take part in training in order to increase competence and broaden employee insights.